2021
DOI: 10.1094/pdis-09-20-1980-re
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure ofPlasmodiophora brassicaePopulations Virulent on Clubroot Resistant Canola (Brassica napus)

Abstract: Clubroot, caused by Plasmodiophora brassicae Woronin, is a significant threat to the canola (Brassica napus L.) industry in Canada. Clubroot resistance has been overcome in more than 200 fields since 2013, representing one of the biggest challenges to sustainable canola production. The genetic structure of 36 single-spore isolates derived from 12 field isolates of P. brassicae collected before and after the introduction of clubroot resistant (CR) canola cultivars (2005-2014) was evaluated by simple sequence re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Thirty-eight P. brassicae single-spore isolates were included in this study. The isolation of purified genomic DNA from resting spores used in our study was previously reported [ 33 ]. The DNA was quantified with a Qubit 2.0 DNA HS Assay (Thermo Scientific, Waltham, MA, USA) and DNA quality was assessed with a TapeStation Genomic DNA Assay (Agilent Technologies, Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Thirty-eight P. brassicae single-spore isolates were included in this study. The isolation of purified genomic DNA from resting spores used in our study was previously reported [ 33 ]. The DNA was quantified with a Qubit 2.0 DNA HS Assay (Thermo Scientific, Waltham, MA, USA) and DNA quality was assessed with a TapeStation Genomic DNA Assay (Agilent Technologies, Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, PI dye solution was added to stain the nuclei, and the cells were placed on ice for 30.0 min. The nuclei were visualized by a microscope [ 24 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Fuling, China, clubroot is one of the main diseases in the production of tumorous stem mustard, which is the main factor threatening the development of the pickle industry. P. brassicae is an obligate parasite soil-borne plant pathogen, that causes root galls or clubs, resulting in water and nutrient absorption disorders, causing foliar wilting and even plant death, and ultimately, major yield losses in crop plants ( Askarian et al, 2021 ). Management of clubroot is mainly through resistant varieties and chemical fungicides ( Peng et al, 2014 ; Niemann et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%